LITERATURE RIVIEW KONTRIBUSI GURU PAI DALAM PENGEMBANGAN KARAKTER KEPRIBADIAN PESERTA DIDIK - Muhammad Agung Amrullah; Badrani Dhyal Haqqi; Rahmi Anekasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the role of Islamic Religious Education (IRE) teachers in the character development of students. The method employed in this study is a literature review, analyzing ten relevant journal articles published between 2015 and 2025. The findings of this study indicate that PAI teachers play a crucial role in shaping students’ character, morals, and religious attitudes through setting a good example, fostering religious practices, moral guidance, and instilling religious values such as discipline, honesty, responsibility, and politeness. Furthermore, Islamic Education teachers do not merely act as conveyors of religious learning materials but also serve as mentors, motivators, and positive role models for students in their daily lives. Additionally, Islamic education plays a role in the spiritual and mental development of students so that they can adapt to the changing times and the influences of their surroundings. In practice, PAI teachers face various challenges, such as the impact of digital media, the social environment, and a lack of support from families. Therefore, collaboration between schools, teachers, and families is necessary to support the character development of students. This study concludes that PAI teachers play a significant role in creating a generation that is religious, possesses good moral character, and is responsible within society.